Whey proteins - facts and possibilities in modern medicine - Mitrović, Nikola; Tasić , Nebojša; Mitrović, Miroslav; Milanović , Nina (Medicinski časopis, 2023)
The values of whey as a healthy and therapeutically useful drink are well known, and in folk medicine it is often attributed miraculous powers and possibilities. This is nothing new, bearing in mind that 460 BC, the father of medicine Hippocrates emphasized the value of whey in the treatment of tuberculosis, jaundice, diseases of the liver and digestive system, skin diseases and many other diseases. Whey is obtained during milk processing and cheese production, where it is present in almost 90% of the total mass. The composition of whey is specific. Water makes up to 93% of the composition, the rest consists of sugars and minerals, B vitamins, as well as a great wealth of probiotic bacteria. Whey is the largest source of essential amino acids compared to plant or animal sources. The concentration of amino acids in whey is 43% compared to oats (21%), wheat husk (21%) and wheat (22%), milk 39%, casein 34% and eggs 32%) or meat proteins (38%). Whey proteins contain almost 50% of essential amino acids and about 26% of branched-chain amino acids. Their composition is similar to the amino acid composition of human muscles, which allows their faster absorption than other sources of protein. The share of free amino acids in whey is 4 to 10 times higher than in milk. They have significant effect on protein synthesis and very strong anabolic effect in the body. Whey amino acids stimulates skeletal muscle regeneration, reduces fatigue, increases synthesis, and reduces muscle protein breakdown. Whey proteins increase the levels of antioxidant enzymes, especially glutathione and catalase. Positive effect on the reducing of the levels TBARS (thiobarbituric acid reactive substance) is important indicator of the decreasing process of lipid peroxidation. Reduction of oxidative stress process in the liver, have positive consequences of inflammation and the content of lipids in the liver tissue and atherosclerosis process.  Recent research indicates a positive effect on glucose metabolism, improving insulin sensitivity and preventing the development of fatty liver syndrome and type 2 diabetes. It has a positive effect on weight control, so whey proteins are integral parts of healthy medical diets, sport drinks with approved efficacy in obesity treatments’. Essential amino acids also act as neurogenic active substances, and are also known as precursors of biogenic amines and neurotransmitters, so it is logical that there is a growing interest in researching their potential in psychiatry.